Baseline Assessment of Rice Production Practices in Selected Barangays of Cawayan, Masbate, Philippines - Ibañez, Jr. , Roger Y.; Velza, Jacob Frederick P.; Barsaga, Martony; Bartolay, Riza (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This descriptive study was conducted to obtain baseline data on the rice production practices in the identified barangays of Cawayan, Masbate for the government to offer real-time intervention. A structured survey questionnaire was used to gather information on the socio-demographic characteristics and rice production practices of the farmers. Aging farmers in the three barangays of Cawayan were observed with an age ranging from 50–60 years old. About 61% of them are classified as small-scale farmers and been tilling the land for more than 31 years. Despite the years they have been in farming, they still belong to the poorest sector with a monthly family income of PHP 800.00. About 96% of the farms in the identified barangays are rain-dependent. Majority of the farmers find difficulty in identifying the variety they are using, and 73% of them used seeds from their previous harvest as planting materials. Land preparation is done through the use of animal-drawn plows and employs direct seeding to minimize expenses. The manual method of controlling weeds, insect pests, and harvesting was practiced by the farmers. The application of fertilizer employed by the farmers is not based on the recommended rate. In totality, farmers obtained breakeven or negative income from their production. The gaps in the farming practices of the farmers can be filled through a holistic and sustainable extension program like Mag-Uma Kaupod ang Pamilya (Farming Together with the Family) in which family members are involved in agricultural production to achieve sufficient and sustainable food for all.